Public participation in Integrated Water Management: A Wicked Process for a Complex Societal Problem - Ker Rault, Philippe Ange (Cranfield University, 2008)
The meaning of both Integrated Water Management and Public Participation (PP) are subject to interpretation by stakeholders, because the concepts of uncertainty, risk management and construction of a societal project challenge scientific expertise, political power and democratic decisions concerning public good management. I do not study PP and IWM with a normative aspiration to identify the ‘true’ problem and participation, but to investigate constructions of reality of water management challenges (WMCs) and of participation from different perspectives: which type of participation is perceived as appropriate for which type of water management challenges? The study areas are river basins in Jordan, Lebanon, Syria and Turkey. The EU Water Framework Directive provides an analytical framework to study meanings of PP in River Basin Management Plan. Grounded Theory Methodology is used to elicit understandings of both PP and WMCs via qualitative and quantitative data (questionnaires, interviews, medium-scale survey). This thesis presents grounded typologies of objectives of PP, types of PP, of WMCs, of the roles of the competent authority and of hurdles to initiate PP. Even in countries where criteria characterising a democratic society are not all entirely satisfied there is a case for promoting PP in IWM. Although an uneducated public, with poor knowledge of the far reaching consequences of WMC is seen as a hurdle to initiate PP, the evidences show the contrary: a public aspiration, readiness and willingness to express ones’ voice. Conditions to foster PP require both political stability and an open society where opinions can be formed and exchanged; but also pressure on resources and services for the public to be interested and willing to take part in water management, and for the competent authority to be willing to engage with both stakeholders and the public in order to complement experts’ understandings of complex societal problems. Public Participation is not only about the pursuit of power over the final decision, but about defining what problems are about according to different constructs of reality. The newly developed grounded typologies of objectives of PP and of types for PP help identifying appropriate forms of participatory practices in relation to the contextual water management crisis.